PEMANFAATAN LIMBAH ORGANIK DAN KOTORAN KAMBING UNTUK PEMBUATAN PUPUK ORAGNIK PADAT DI DESA SEI KAMAH II KABUPATEN ASAHAN - Ade Fipriani Lubis; Tri Arya Ardika; Intan Agi Pramudita; Ayuka Dwi Surya (Smart Education, 2025)
Abstract: The utilization of organic waste and animal manure (kohe), goat manure is one alternative solution in supporting sustainable agriculture and reducing environmental pollution. This community service aims to study the process of making solid organic fertilizer from a combination of household organic waste with goat manure and assess the resulting quality. The method used is aerobic fermentation with the addition of microbial activators to accelerate decomposition. This series of activities is part of one of the activities of the 2025 KKN students of the Faculty of Agriculture, Asahan University. This activity is a socialization and field practice activity together with housewives, and PKK mothers of Sei Kamah II Village. The expected output of the socialization activity regarding the utilization of organic waste and goat manure is a solid organic fertilizer that has a loose texture, blackish brown in color, and is free from strong odors. In addition to producing organic fertilizer products, this activity also has a positive impact in the form of increasing knowledge and skills in the community to process household waste and goat manure into useful products.Â Keywords: Organic Waste, Goat Manure, Solid Organic Fertilizer, Community Empowermen.Â Abstrak: Pemanfaatan limbah organik dan kotoran hewan (kohe), kotoran kambing merupakan salah satu alternatif solusi dalam mendukung pertanian berkelanjutan dan mengurangi pencemaran lingkungan. Pengabdian ini bertujuan untuk mengkaji proses pembuatan pupuk organik padat dari kombinasi limbah organik rumah tangga dengan kohe kambing serta menilai kualitas yang dihasilkan. Metode yang digunakan adalah fermentasi aerob dengan penambahan aktivator mikroba untuk mempercepat dekomposisi. Rangkain kegiatan ini merupakan, bagian dari salah satu kegiatan mahasiswa KKN 2025 Fakultas Pertanian Universitas Asahan. Kegiatan ini merupakan kegiatan sosialisasi dan praktik lapangan bersama dengan ibu rumah tangga, dan ibu-ibu PKK Desa Sei Kamah II. Luaran yang diharapkan dari kegiatan sosialisasi mengenai pemanfaatan limbah organik dan kotoran kambing berupa pupuk organik padat yang memiliki tekstur gembur, berwarna coklat kehitaman, dan bebas dari bau menyengat. Selain menghasilakan produk pupuk organik, kegitan ini juga memberikan dampak positif berupa peningkatan pengetahuan dan keterampilan masyarakat dalam mengelolah limbah rumah tangga dan kohe kambing menjadi produk bernilai guna.Â Kata Kunci: Limbah Organik, Kohe Kambing, Pupuk Organik